Ozone Determination: A Comparison of Quantitative Analysis Methods - Rachmat Triandi Tjahjanto; Dhesy Galuh R.; Sri Wardhani (The Journal of Pure and Applied Chemistry Research, 2012)
A comparison of ozone quantitative analysis methods by using spectrophotometric and volumetric method has been studied. The aim of this research is to determine the better method by considering the effect of reagent concentration and volume on the measured ozone concentration. Ozone which was analyzed in this research was synthesized from air, then it is used to ozonize methyl orange and potassium iodide solutions at different concentration and volume. Ozonation was held for 20 minutes with 363 mL/minutes air flow rates. The concentrations of ozonized methyl orange and potassium iodide solutions was analyzed by spectrophotometric and volumetric method, respectively. The result of this research shows that concentration and volume of reagent having an effect on the measured ozone concentration. Based on the results of both methods, it can be concluded that volumetric method is better than spectrophotometric method.